Kajian Ekokritik dalam Novel Kisah Seekor Camar dan Kucing yang Mengajarinya Terbang Karya Luis Sepulveda - Vita Diah Setyoningrum,; Mustaqim, Akhmad; Muslimah, Adisha Nur Izzatil; Septian, Mohammad Imam Ghozali Fajar (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research aims to discuss ecocriticism in the novel The Story of a Seagull and the Cat Who Taught Him to Fly. The focus of this research is on human behavior toward the environment, the impact of human behavior on nature, and the form of environmental awareness raised by the author. The methodology used is descriptive qualitative. The data collection stages in this study, namely 1) reading the data source repeatedly; 2) recording data based on the focus of research; 3) data that has been obtained, then sorted according to the needs of research; 4) data analyzed using ecocritical theory; and 5) drawing conclusions. The results show that human behavior that is taken for granted has harmed other creatures and has an impact on the surrounding environment. However, the author also offers a solution through the form of care described.